Global trends of modernization in budgeting and finance - Ushakov, D. S. (Denis Sergeevich) (Business Science Reference, 2019)
"This book analyzes corporate finance and alternative approaches for financial management and management accounting. It also explores financial globalization and its consequences: the political, legal, economic, and social aspects"--